ANALYSIS OF EFL STUDENT’S DIFFICULTIES IN DETERMINING OF THE TITLE OF ENGLISH THESIS - Nur Widad Wijaya; Nur Lailatul Badriyah; Nurul Faizah; Nurul Ismah; Rafika; Ratna Yunita; Rifqatun Zakiyyah; Rifki Fuadi (Educazione: Journal of Education and Learning, 2024)
The phenomenon of difficulty for English as a Foreign Language (EFL) students in determining the title of their thesis in English indicates the existence of complex academic problems in the early stages of research. This study aims to analyze in depth the factors that affect these difficulties and understand the dynamics of student experience in formulating research titles. This study departs from the reality of low academic literacy, conceptual confusion, and dependence on supervisors which often hinder the process of determining titles. The research uses a qualitative approach with a case study type, through in-depth interview techniques, documentation, and findings in the field. The results of the study show that the limitation of academic literacy causes students to have difficulty identifying research gaps, while conceptual confusion hinders the sharpening of the focus of the study, and dependence on lecturers reduces academic independence. These three factors are interrelated and form a pattern of recurring difficulties. The implications of this study emphasize the importance of strengthening scientific literacy, developing conceptual skills, and creating a more dialogical guidance pattern to improve the quality of determining the thesis title of EFL students in a more systematic and reflective manner.